70% Trichloroacetic Acid in the Treatment of Facial Sebaceous Hyperplasia - Chiriac Anca; Brzezinski Piotr; Năznean Adrian; Podoleanu Cristian; Stolnicu Simona (Journal of Interdisciplinary Medicine, 2018)
The present paper highlights the usefulness of 70% trichloroacetic acid in treating sebaceous hyperplasia in elderly patients. Esthetics are an important issue, and different therapeutic modalities can be used, such as systemic isotretinoin, surgical excision, electrocautery, cryosurgery, topical photodynamic therapy and laser, but all these methods are expansive and invasive procedures that may result in scars, which are more extensive than the original lesions.